2023
DOI: 10.3390/healthcare11141980
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Factors Associated with Motivation to Quit Vaping among Vapers in the Federal Territory of Kuala Lumpur, Malaysia

Lei Hum Wee,
Jo Ann Andoy Galvan,
Sapna Shridhar Patil
et al.

Abstract: The prevalence of vaping worldwide is showing an upward trend. This study aimed to determine the factors associated with motivation to quit vaping among vapers in the Federal Territory of Kuala Lumpur, Malaysia, through a cross-sectional, purposive sampling study. Respondents were required to complete a questionnaire consisting of vapers’ sociodemographic questions, habitual behavioral pattern questions, the e-Fagerström Test of Nicotine Dependence, the Glover–Nilsson Smoking Behavioral Dependence Questionnair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…25,26 Finally, the results of this study showed that consistently across all models, nicotine dependence was significantly associated with a lower motivation to quit EC use. Similarly, a study among US adolescent vapers showed that those with higher nicotine dependence had lower intention to quit EC, 27 whilst another study among university students in Malaysia showed that motivation to quit EC for those with mild to high nicotine dependence compared to those with no dependence. 28 This may be because having a higher nicotine dependence makes withdrawal symptoms worse when one ceases the nicotine intake.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…25,26 Finally, the results of this study showed that consistently across all models, nicotine dependence was significantly associated with a lower motivation to quit EC use. Similarly, a study among US adolescent vapers showed that those with higher nicotine dependence had lower intention to quit EC, 27 whilst another study among university students in Malaysia showed that motivation to quit EC for those with mild to high nicotine dependence compared to those with no dependence. 28 This may be because having a higher nicotine dependence makes withdrawal symptoms worse when one ceases the nicotine intake.…”
Section: Discussionmentioning
confidence: 98%
“… 28 This may be because having a higher nicotine dependence makes withdrawal symptoms worse when one ceases the nicotine intake. 27 However, the strength of its association with motivation to quit EC use was consistently attenuated when source credibility of media and trustworthiness of online media were added into the last step of the hierarchical regression model. Thus, searching for health information may be influential in increasing motivation to quit EC use in our study sample.…”
Section: Discussionmentioning
confidence: 99%